2022
DOI: 10.1080/13880209.2022.2112239
|View full text |Cite
|
Sign up to set email alerts
|

Kirenol alleviates diabetic nephropathy via regulating TGF-β/Smads and the NF-κB signal pathway

Abstract: Context Kirenol possesses anti-inflammatory, antifibrotic and anti-arthritic effects. However, its reno-protective effects against diabetic nephropathy (DN) have not been evaluated. Objective This study explores the reno-protective effects of kirenol against DN and clarifies the potential mechanisms. Materials and methods The mesangial cells were treated with 20 µM kirenol and 10 ng/mL human recombinant TGF-β1 or 30 mM glucose for 24 h. Then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Recent evidence has indicated that some inflammatory cytokines such as IL-1β, IL-6, MCP-1, TNF-α, and TGF-β1 played a critical role in hyperglycaemia-induced renal injury. 14 , 15 Therefore, inhibiting inflammatory responses and reducing the expression of cytokines will effectively improve renal injury and enhance renal function in DN. Previous researches have demonstrated that TLR4/NF-κB as crucial pathway had played crucial role in the DN by mediating immune inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence has indicated that some inflammatory cytokines such as IL-1β, IL-6, MCP-1, TNF-α, and TGF-β1 played a critical role in hyperglycaemia-induced renal injury. 14 , 15 Therefore, inhibiting inflammatory responses and reducing the expression of cytokines will effectively improve renal injury and enhance renal function in DN. Previous researches have demonstrated that TLR4/NF-κB as crucial pathway had played crucial role in the DN by mediating immune inflammatory response.…”
Section: Introductionmentioning
confidence: 99%